Розвиток державно-приватного партнерства в процесі вдосконалення планування та бюджетування на підприємстві - Аль-Шаргі Фахд (Культура народов Причерноморья, 2014)
У статті розглянуті основні етапи побудови збалансованої системи показників для
стратегічного планування проектів державно-приватного партнерства. Визначені взаємозв'язки
стратегічного і оперативного планування з бюджетуванням на підприємстві. Запропонована система
заходів щодо реалізації стратегії розвитку на підприємстві. Проведена оцінка ефективності реалізації
стратегії розвитку підприємства. В статье рассмотрены основные этапы построения сбалансированной системы
показателей для стратегического планирования проектов государственно-частного партнерства.
Определены взаимосвязи стратегического и оперативного планирования с бюджетированием на
предприятии. Предложенная система мероприятий по реализации стратегии развития на
предприятии. Проведена оценка эффективности реализации стратегии развития предприятия. The article under consideration deals with the principle stages of the balanced scorecard for strategy
planning of the projects of public – private partnership. Relationship defined strategic and operational planning
with budgeting in the enterprise. The proposed system of measures to implement the development strategy of the
company. Assessed the effectiveness of the implementation of enterprise development strategies. In the process of
establishing causal relations objectives of the strategic and operational planning, cascading in their divisions
for a systematic approach to project management. The proposed approach provided an opportunity to develop
measures for the formation and implementation of enterprise development strategies.Was assessed contribution
to achieving this goal in the implementation strategy. The proposed approach has the opportunity to develop a
series of activities to implement the strategy of the enterprise. Based on empiric experience offered basic
prospects development strategy. These include: "Finance", "Customers ", " Business Processes ", " Innovation ",
" Regional Development ".